Availability of Consumer Prices for Bunion Surgery. (December 2014) - Willey, James C.; Reuter, Lainee S.; Belatti, Daniel A.; Phisitkul, Phinit; Amendola, Ned
Background: Today, insurance insulates most patients from the true costs of the health care services they consume. Economists believe that the absence of price signals incentivizes patients to pursue more extensive care than they would otherwise. Reformers propose restoring price consciousness to patients as a way to tame the soaring costs of American health care. To test this idea, we decided to gauge the availability and variability of price quotes for a common elective surgery—bunion repair. Methods: Orthopedic clinics were sorted by state and randomly selected from an online directory maintained by the American Orthopaedic Foot and Ankle Society. Each selected clinic was contacted up to 3 times in an attempt to get a full, bundled price quote using a standardized patient script. If this was unavailable, an isolated quote for the physician fee alone was solicited. Results: Of the 141 clinics contacted, 56 (39.7%) could provide a physician price estimate and 12 (8.5%) could give a complete bundled estimate, including hospital fees. The overall mean bundled price quoted was $18 332, while the overall mean physician fee quoted was $2487. There was no statistically significant difference in the mean price quoted by academic and private clinics, nor was regional variation observed. Conclusion: We found low price availability for elective bunion procedures. Clinical Relevance: However, the wide variation observed in the prices that were quoted suggests that a very determined patient may be able to spend substantially less on an elective surgery if they were willing to select a provider carefully.